Prevention of adolescent stimulant drug use: Do the home life environment and extracurricular activities influence this? Findings from the Irish Planet Youth Survey - Fionn P. Daly; Seán R. Millar; Emmet Major; Peter M. Barrett (PLoS ONE, 2025)
Introduction Stimulant drug use during adolescence (e.g., cocaine or ecstasy) can lead to a myriad of adverse health effects, but it remains uncertain how the home life environment and involvement in structured extracurricular activities may correlate with teenage stimulant use. Methods We conducted an analysis utilising data from the 2020 Planet Youth survey, an anonymous questionnaire administered to school-going adolescents in the western region of Ireland. All adolescents with complete demographic information on age, gender and drug use were included in the analysis. Multivariable-adjusted logistic regression was used to explore factors associated with adolescent lifetime cocaine or ecstasy use. Exposure variables of interest were factors associated with the home environment (parental rule-setting, parental monitoring, being outside after midnight), mental health, intergenerational closure (defined as the extent of connectedness between adolescents and their peers, parents of their peers, and between parents themselves) and adolescent participation in extracurricular activities (sports, arts, volunteering, and/or afterschool clubs). Limitations of this study included its cross-sectional design which precluded causal inferences, self-reported data which may lead to information and social desirability biases, respectively, as well as adolescents who were not enrolled in formal education being excluded from the sampling frame. Results In total, 167 out of 4890 (3.4%) and 136 out of 4895 (2.8%) adolescents had previously used cocaine and ecstasy, respectively. Almost half of the participants in both datasets were female (49.7%), and the majority were aged 16 years (62.8% and 62.7% of the cocaine and ecstasy samples, respectively). Being outside after midnight during the previous week was associated with lifetime stimulant use (cocaine AOR = 5.63, 95%CI: 3.98,7.97; ecstasy AOR = 6.37, 95%CI: 4.36,9.30) (vs. never). Adolescents who reported “bad/very bad” mental health had over three times the odds of previous cocaine use (AOR = 3.63, 95%CI: 2.39, 5.49), and over five times the odds of previous ecstasy use (AOR = 5.15, 95%CI: 3.09, 8.59) (vs. “good/very good”). A lack of parental rule-setting (cocaine AOR = 1.28, 95%CI: 1.10, 1.50; ecstasy AOR = 1.39, 95%CI: 1.17,1.64), lack of parental monitoring (cocaine AOR = 1.81, 95%CI: 1.58,2.06; ecstasy AOR = 2.15, 95%CI: 1.86, 2.48), and reduced intergenerational closure (cocaine AOR = 1.37, 95%CI: 1.18,1.58; ecstasy AOR = 1.57, 95%CI: 1.34,1.83) were associated with lifetime stimulant use. Teenagers who did not participate regularly in sport had increased odds of previous cocaine use (in a club/team AOR = 1.50, 95%CI: 1.06,2.11; outside of a club/team AOR = 1.45, 95%CI: 1.03,2.04) and ecstasy use (in a club/team AOR = 1.54, 95%CI: 1.05,2.27; outside of a club/team AOR = 1.79, 95%CI: 1.56,3.12). Conclusion The prevalence of stimulant use among this sample of Irish adolescents is relatively high by European standards, particularly cocaine use. Reduced parental rule-setting, supervision and family bonding time was associated with higher odds of adolescent stimulant use. Regular involvement in sports may have a protective effect against adolescent stimulant drug use.